Depletion of gut microbiota influents glucose metabolism and hyperandrogenism traits of mice with PCOS induced by letrozole - Li, Yushan; Zhu, Yuchen; Li, Dan; Liu, Wen; Zhang, Yi; Liu, Wei; Zhang, Chenhong; Tao, Tao (Frontiers in Endocrinology, 2023)
Background: Polycystic ovary syndrome (PCOS) is a multifaceted disorder that impacts metabolism, reproduction, as well as endocrine function, characterized by excessive levels of androgen and insulin resistance. The gut microbiota has been implicated in the pathogenesis of PCOS. However, the precise mechanisms through which the gut microbiota influences PCOS still require further elucidation.The PCOS mouse model was established through the administration of letrozole to both conventional and antibiotics-treated mice. The evaluation of glucose metabolism, sex hormone levels, and ovarian morphology was conducted. Furthermore, the fecal samples from each group of mice were subjected to 16S rRNA gene sequencing, and functional prediction of gut microbiota was proceeded using PICRUSt2 to explore potential mechanisms.Results: By using letrozole-induced PCOS mice model, we manifested that antibiotic intervention significantly reduced the serum total testosterone level and ameliorated glucose intolerance.Antibiotic treatment reduced the number of amplicon sequence variants (ASVs), as well as the Shannon and Simpson index. Meanwhile, letrozole induced a significant increase in the Shannon and Simpson index instead of ASVs. Through random forest model analysis, the results revealed significant alterations in three distinct groups of microbiota, namely Clostridia_vadinBB60_group, Enterorhabdus, and Muribaculaceae after letrozole treatment. Further correlation analysis revealed a This is a provisional file, not the final typeset article positive association between alterations in these microbiota and both serum total testosterone levels and the area under the curve (AUC) of blood glucose in IPGTT. The administration of antibiotics led to a decrease in the absolute abundance of 5 ASVs belonging to unclassified Clostridia_vadinBB60_group, unclassified Enterorhabdus, and unclassified Muribaculaceae, which exhibited a positive correlation with the levels of total testosterone in mice serum, as well as the area under the curve of blood glucose in IPGTT. Moreover, 25 functional pathways of gut microbiome were significantly discrepant between the letrozole-treated mice with and without antibiotics.These results suggest that disturbance of the gut microbiota may take participate in the progression of PCOS and manipulating the composition of the gut microbiota may be a therapeutic approach for managing PCOS.